What we have learned: implementing MiniLit as an intervention with young struggling readers. Issue 2 (3rd July 2021) - Reynolds, Meree; Buckingham, Jennifer; Madelaine, Alison; Arakelian, Sarah; Bell, Nicola; Pogorzelski, Simmone; Wheldall, Robyn; Wheldall, Kevin
ABSTRACT: Information about effective interventions for students with early reading difficulties is essential when deciding about how best to provide support. MiniLit, a small-group intervention for young struggling readers, was released in 2011 after several years of development and trials. This paper provides a rationale for MiniLit, a brief history of its development and implementation, and a summary of evidence collected from various efficacy studies. Pre- and post-test group data from program trials and experimental research indicate that MiniLit has produced large gains in students' phonemic awareness, phonic decoding, word reading, and spelling. Experimental studies yielded lower effect sizes than program trials for phonic decoding and word reading skills, with effect sizes for these dimensions in the medium or large range. Program revisions in response to evidence from studies, feedback from practitioners, and findings from recent research about early reading have been undertaken, resulting in the development of MiniLit Sage.